2021
DOI: 10.3390/cancers13215412
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Effect of the BMP9–ALK1 Pathway in Blood Vessels: An Opportunity for Cancer Therapy Improvement?

Abstract: The improvement of cancer therapy efficacy, the extension of patient survival and the reduction of adverse side effects are major challenges in cancer research. Targeting blood vessels has been considered a promising strategy in cancer therapy. Since the tumor vasculature is disorganized, leaky and triggers immunosuppression and tumor hypoxia, several strategies have been studied to modify tumor vasculature for cancer therapy improvement. Anti-angiogenesis was first described as a mechanism to prevent the form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 169 publications
(239 reference statements)
0
11
0
Order By: Relevance
“…Although our previous studies demonstrate a role of ALK1 in regulating ECM production by ECM producing cells like fibroblasts, the biological role of ALK1 has been traditionally considered more relevant in the regulation of endothelial cell balance during development, cardiovascular diseases and tumor angiogenesis ( Ayuso-Inigo et al, 2021 ). To understand ALK1 function in tissue fibrosis is very important to consider two molecular players that regulate ALK1 activity: Its high affinity ligand BMP9 ( David et al, 2007b ) and the coreceptor endoglin ( Lebrin et al, 2004 ; López-Novoa and Bernabeu, 2010 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although our previous studies demonstrate a role of ALK1 in regulating ECM production by ECM producing cells like fibroblasts, the biological role of ALK1 has been traditionally considered more relevant in the regulation of endothelial cell balance during development, cardiovascular diseases and tumor angiogenesis ( Ayuso-Inigo et al, 2021 ). To understand ALK1 function in tissue fibrosis is very important to consider two molecular players that regulate ALK1 activity: Its high affinity ligand BMP9 ( David et al, 2007b ) and the coreceptor endoglin ( Lebrin et al, 2004 ; López-Novoa and Bernabeu, 2010 ).…”
Section: Discussionmentioning
confidence: 87%
“…We observed lower vascular rarefaction in Alk1 +/− mice after 3 days of UUO. ALK1 regulates negatively the activation phase of angiogenesis ( Ayuso-Inigo et al, 2021 ) and it is expected that lower levels of ALK1 in Alk1 +/− mice lead to a maintained angiogenic phase or an impaired vessel regression phase, which also correlates with the higher VEGF levels observed in O kidneys from Alk1 +/− mice. Our observations are in concordance with those of Sharpfenecker et al (2011), who demonstrated in a kidney fibrosis model after irradiation that Alk1 +/− mice show lower vascular injury after 20 weeks of irradiation, and this correlated with higher levels of VEGF and VEGFR2 at that time point ( Scharpfenecker et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that BMP9 is a crucial factor inducing the malignant nature of HCC and found that BMP9-ID1 signaling promotes cancer stem cell properties in EpCAM-positive HCC cells by activating Wnt/β-catenin signaling [9]. The role of BMP9 in angiogenesis is still controversial [14]; thus, we aimed to investigate the functional roles of BMP9 signaling in the activation of angiogenic signaling in HCC cells in the current study.…”
Section: Discussionmentioning
confidence: 98%
“…What is exciting is that some active ingredients from TCM need to be relocated in angiogenic effects for the shared signaling pathways (such as MAPK and PI3K/Akt/mTOR), implying the viability of co-targeting angiogenesis and other phenotypes, including proliferation, apoptosis, and stem cell like-type. However, there are few studies to demonstrate the role of candidate molecules toward antiangiogenic factors or signalings, such as TNFα, TSP-1, TIMP, and TGF-β/BMP pathway ( Ayuso-Íñigo et al, 2021 ), but IL-8 seems to involve the crosstalk between angiogenesis and TME like VEGF ( Fousek et al, 2021 ). In clinical, these candidate drugs were more considered dietary supplements or adjuvants ( Table 3 ) for the anti-angiogenic strategy, beyond a single drug being used.…”
Section: Perspectives and Conclusionmentioning
confidence: 99%